Differential Viral Load Indicates HDV Influences HBV Replication in HBV/HDV Coinfected Patients (Molecular Medicine Communications, 2022)
Viral Hepatitis causing approximately 1.4 million deaths every year. HBV is a partially double stranded DNA virus and belongs to the family Hepadnaviridae. HDV is a sub satellite virus which infects patients that are already infected by HBV because it depends on HBV surface antigen for its replication. HDV causes super infection with different complexities as compared to sole HBV infection.To compare viral load of HBV and HDV to check possible influence on each others replication.A cross-sectional analytical study was conducted on 907 samples. HBV DNA was detected and quantified by Abbott HBV Quantification kit and HDV RNA was detected and amplified by RoboGene®. Screening of HDV RNA and HBV DNA by PCR and results were analyzed using SPSS. Out of  907 patients, 33% were HBV/HDV co-infected, 35%  were HBV, 18% were infected with HDV & 14% were HBV/HDV negative.Out of these, 75.7% were males and 24.3% were females. The patients were divided into three age groups: 5-20 years, 21-40 years & 41-80 years. Overall levels of HBV DNA PCR < 1000 IU/ml was found in 74% HBV/HDV co-infected patients as compared to 30.8% HBV mono infected. This study indicates that the absence or the low viral load of HBV in HDV positive patients might be due to possible subdue of HBV by HDV in HBV/HDV co-infected patients.Age group of 20-40 years and male gender is comparatively at high risk for these viral infections.
Keywords: Hepatitis B virus; Hepatitis D virus; Suppression; HBV/HDV Co-infection